Chasing Snowflakes: Tourists’ Winter Tales of Wonder, Motivation, and Challenges in Georgia and Armenia - Haguisan III, Ismael A. (Philippine Social Science Journal, 2025)
This narrative inquiry explores the immersive winter tourism appeal of Georgia and Armenia through the experiences of two seasoned Filipino travelers. Utilizing unstructured interviews and thematic analysis, the study reveals that the regions’ stunning snowscapes, rich heritage, and warm hospitality significantly outweigh minor logistical and language challenges. These findings position Georgia and Armenia as premier winter destinations, recommending that future tourism strategies focus on optimizing infrastructure, accommodation, and language support to further enhance visitor satisfaction and sustainable sector growth.